Intergenerational transfer of antibiotic-perturbed microbiota enhances colitis in susceptible mice. (February 2018) - Schulfer, Anjelique; Battaglia, Thomas; Alvarez, Yelina; Bijnens, Luc; Ruiz, Victoria; Ho, Melody; Robinson, Serina; Ward, Tonya; Cox, Laura; Rogers, Arlin; Knights, Dan; Sartor, R.; et al.
Abstract Antibiotic exposure in children has been associated with the risk of inflammatory bowel disease (IBD). Antibiotic use in children or in their pregnant mother can affect how the intestinal microbiome develops, so we asked whether the transfer of an antibiotic-perturbed microbiota from mothers to their children could affect their risk of developing IBD. Here we demonstrate that germ-free adult pregnant mice inoculated with a gut microbial community shaped by antibiotic exposure transmitted their perturbed microbiota to their offspring with high fidelity. Without any direct or continued exposure to antibiotics, this dysbiotic microbiota in the offspring remained distinct from controls for at least 21 weeks. By using both IL-10-deficient and wild-type mothers, we showed that both inoculum and genotype shape microbiota populations in the offspring. Because IL10−/− mice are genetically susceptible to colitis, we could assess the risk due to maternal transmission of an antibiotic-perturbed microbiota. We found that the IL10−/− offspring that had received the perturbed gut microbiota developed markedly increased colitis. Taken together, our findings indicate that antibiotic exposure shaping the maternal gut microbiota has effects that extend to the offspring, with both ecological and long-term disease consequences. Inoculation of pregnant dams with an antibiotic-perturbed microbiota resulted in vertical transmission to the offspring in the absence of antibiotics and increased colitis in IL10–/– mice, indicating that antibiotic treatment has long-term effects.